Substantia Nigra D(1) Receptors and Stimulation of Striatal Cholinergic Interneurons by Dopamine: A Proposed Circuit Mechanism - Abercrombie, Elizabeth D. (J Neurosci, 1997)
Dopamine release can regulate striatal acetylcholine effluxin vivo through at least two receptor mechanisms: (1) direct inhibition by dopamine D(2) receptors on the cholinergic neurons, and (2) excitation initiated by dopamine D(1) receptors. The neuroanatomical locus of the latter population of D(1) receptors and the pathway(s) involved in the expression of their influence are controversial issues. We have tested the hypothesis that D(1) receptors in substantia nigra pars reticulata are involved in the excitatory component of dopaminergic actions on striatal acetylcholine output. In vivo microdialysis was used in awake rats. Infusion of the selective D(1) receptor agonistR(+)-1-Phenyl-2,3,4,5-tetrahydro-1H-3-benzazepine-7,8-diol (SKF 38393) hydrochloride into pars reticulata of substantia nigra elicited a significant increase in striatal acetylcholine efflux. Likewise, d-amphetamine applied into pars reticulata of substantia nigra by reverse dialysis produced an elevation in acetylcholine output measured at a second microdialysis probe in the striatum. Application of d-amphetamine in the striatum by reverse dialysis elicited a decrease in striatal acetylcholine efflux that could be reversed subsequently by local application ofd-amphetamine in substantia nigra pars reticulata. A 2 mg/kg intraperitoneal dose of d-amphetamine, which has no net effect on striatal acetylcholine output under control conditions, elicited a significant decrease in acetylcholine efflux when the D(1) receptor antagonistR(+)-7-Chloro-8-hydroxy-3-methyl-1-phenyl-2,3,4,5-tetrahydro-1H-3-benzazepine (SCH 23390) hydrochloride was applied simultaneously via a second microdialysis probe in substantia nigra pars reticulata. Thus, an excitatory D(1)-mediated influence on striatal acetylcholine output is initiated in substantia nigra pars reticulata, and this influence contributes to the effects of indirect dopaminergic agonists such as d-amphetamine on striatal acetylcholine efflux. These results indicate an important role of somatodendritic dopamine release, in addition to nerve terminal dopamine release, in the regulation of activity in basal ganglia circuits.